Badanie ASCOT potwierdza korzyści wynikające ze stosowania nowych klas leków hipotensyjnych - Pasierski, Tomasz (Przewodnik Lekarza/Guide for GPs, 2005)
Dahlöf B, Sever PS, Poulter NR, et al. Prevention of cardiovascular events with an antihypertensive regimen of amlodipine adding perindopril as required versus atenolol adding bendroflumethiazide as re – quired, in the Anglo-Scandinavian Cardiac Outcomes Trial-Blood Pressure Lowering Arm (ASCOT-BPLA): a multicentre randomised controlled trial. Lancet online, 4 September 2005.